Elixir of Life: Tulsi (Ocimum sanctum L.) and occurrence of Powdery Mildew - Patel, Naved K.; Hedawoo, Ganesh B. (Indian Journal of Integrative Medicine, 2022)
Background: India has rich diversity of medicinal plants distributed in different geographical and environmental conditions. The traditional medicinal practices are an important part of the primary healthcare system in the developing world. Tulsi (Ocimum sanctum L.) is one of the aromatic, perennial plant. It is cultivated for religious and traditional medicine purposes and for its essential oil. Within Ayurveda, Tulsi is known as “Mother medicine of Nature” and is revered as an “Elixir of Life”. Objective: Various pathogens like fungi adversely affect the medicinal plant parts and decrease the medicinal value of the part. Powdery mildew disease is become a serious and widespread problem in many parts of India and abroad. Method: Powdery mildew fungi were identified by observing symptoms, macroscopic and microscopic characters of infected plant material. Result: Oidium ocimi grows superficially on leaves of Tulsi plant. At severity of infection causes morphological, anatomical and physiological damages to plants. Conclusion: The incidence of this fungal disease on Tulsi plant may causes a setback to the industry associated with the formulation of its medicinal products..